Inkarnasi Sebagai Penyataan Allah (Eksegesa 1 Yohanes 1: 1-4) - Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2011)
Incarnation is a central teaching in the doctrine of Christology. This topic has become a complex concept to be explained. For centuries this topic has been disputed by whether Christian scholars or the opposite of Christianity parties. Apologetic regarding the incarnation of Christ becomes very important for the Church in history. This article elaborates on the concept of logos (the Word) that has presented as a human being, known as an incarnation. The Methodology that has been used in this article were relevance literature study, textual exegeses, and an interpretation based on hermeneutic principles. From the examination that has been conducted, the author inverted that the incarnation is the chosen “way” for God to reveal the salvation for human beings. Incarnation is the revelation of God as transcendence being become immanence being. This God’s work has been done to provide relationships and atonement for human beings.